The effects of technical factors on the fractal dimension in different dental radiographic images - Mehmet Amuk; Gamze Şirin Sarıbal; Nihal Ersu; Serkan Yılmaz (European Oral Research)
PurposeThe aim of this study was to assess the impact of exposure parameters and image formats on fractal dimension (FD) values in periapical, panoramic, and CBCT images.Materials and MethodsSeven dry male mandibles were selected, and a Gutta-Percha was used to identify identical regions of interest. A periapical radiograph was taken with 60 kVp/7 mA and exported in DICOM, JPEG, TIFF, and PNG formats. Nine periapical radiographs (60, 65, 70 kVp; 4, 5, 6 mA) were taken from seven dry human mandibles. Additionally, 12 panoramic radiographs (60, 70, 81, 90 kVp; 5, 8, 13 mA) and 10 CBCT images (with different scanning options and FOVs) were taken from each mandible. FDs were measured from a standard area.ResultsThe intra-class correlation coefficient demonstrated a high degree of agreement between observers. No significant difference was found between TIFF and PNG formats (p > 0.05). The highest FD mean was found in TIFF format, while the lowest FD mean was found in JPEG format (p < 0.001). There was no significant difference between kVp and mA settings in periapical images. In panoramic images, a significant difference was found at 90 kVp (p = 0.001) and 13 mA (p < 0.001), with lower FD values observed at these settings. There was no significant difference between FOV and resolution in CBCT images (p > 0.05).ConclusionThe format of the image can influence FD. For periapical and panoramic radiographs, kVp and mA settings do not have a significant impact on FD. However, fractal analysis may not be an ideal method for evaluating three-dimensional images, such as those obtained with CBCT.